Posttranslational modifications of cardiac ryanodine receptors: Ca(2+) signaling and EC-coupling - Niggli, Ernst (2012)
In cardiac muscle, a number of posttranslational protein modifications can alter the function of the Ca(2+) release channel of the sarcoplasmic reticulum (SR), also known as the ryanodine receptor (RyR). During every heartbeat RyRs are activated by the Ca(2+)-induced Ca(2+) release mechanism and contribute a large fraction of the Ca(2+) required for contraction. Some of the posttranslational modifications of the RyR are known to affect its gating and Ca(2+) sensitivity. Presently, research in a number of laboratories is focussed on RyR phosphorylation, both by PKA and CaMKII, or on RyR modifications caused by reactive oxygen and nitrogen species (ROS / RNS). Both classes of posttranslational modifications are thought to play important roles in the physiological regulation of channel activity, but are also known to provoke abnormal alterations during various diseases. Only recently it was realized that several types of posttranslational modifications are tightly connected and form synergistic (or antagonistic) feed-back loops resulting in additive and potentially detrimental downstream effects. This review summarizes recent findings on such posttranslational modifications, attempts to bridge molecular with cellular findings, and opens a perspective for future work trying to understand the ramifications of crosstalk in these multiple signaling pathways. Clarifying these complex interactions will be important in the development of novel therapeutic approaches, since this may form the foundation for the implementation of multi-pronged treatment regimes in the future.